Quantification of the biomass and nutrients in the trunk of Eucalyptus grandis at different ages - Silva, H.D. da; Ferreira, C.A.; Bellote, A.F.J. (Center for International Forestry Research, 2001)
The accumulation and cycling of nutrients in planted forest is essential to the establishment of management practices that can lead to the sustainable production of the forest site. The uptake, accumulation and release of nutrients depend on tree age and stage of development. The knowledge of accumulation and cycling of nutrients allows the estimation of output and replacement of nutrients to the forest site. This makes it possible to correct nutritional disorders caused by the use of inadequate management techniques. The usual method of sampling biomass and nutrients is always destructive making it impossible to establish permanent plots for nutritional monitoring. This study aimed at selecting models to estimate the biomass (volume and weight) and the nutrient contents in different parts of the trunk of Eucalyptus grandis, and reducing costs of sampling and analysis. Forty-five trees were selected from the dominant class (15 trees), co-dominant (15 trees) and suppressed (15 trees) in commercial plantations of E.grandis at ages 3, 5 and 7 years, in the municipality of Itatinga, SP, Brazil. Samples were taken of bark, sapwood and heartwood separately. Models to estimate volume and weight in the different components of the trunk were generated from the diameter at breast height (dbh) using regression analysis. Models to estimate content of N, P, K, Ca and Mg in the bark, sapwood and heartwood from the nutrient contents in a section of the trunk were also defined, so enabling a recommendation for non-destructive sampling.